Perioperative Approach to Reducing Hematoma during Rhytidectomy: What Does the Evidence Show?. Issue 6 (10th May 2021) - Cason, Roger W.; Avashia, Yash J.; Shammas, Ronnie L.; Savetsky, Ira L.; Rohrich, Rod J.
Abstract : Background: Postoperative hematoma remains the most common complication in rhytidectomy, prompting surgeons to use a multitude of adjunctive measures to prevent its occurrence. The goal of this systematic review was to determine which of these measures are supported by strong evidence, and to highlight those that remain unsubstantiated and require further investigation. Methods: A systematic search was performed of the PubMed and Embase databases for English literature from 1975 to March of 2020 containing designated keywords, and focusing specifically on adjunctive measures aimed at preventing hematoma in rhytidectomy. The resultant articles were then systematically screened according to predefined inclusion and exclusion criteria to determine eligibility for inclusion in the study. Results: The keyword search yielded a total of 2391 articles. Title and abstract screening resulted in 103 articles that were eligible for full-text review. Ultimately, 48 articles met final inclusion criteria. The articles were categorized into their particular mode of intervention: fibrin tissue sealants, perioperative medications (anesthetics, antihypertensives, miscellaneous medications), and intraoperative maneuvers (hemostatic agents, preinfiltration, intraoperative maneuvers, and drains). Nine studies were indexed as evidence Level II and 24 as evidence Level III. The remainder of studies constituted Level IV evidence. Conclusions: Adjunctive interventions have been borne out of necessity in efforts to reduce postoperative hematoma after rhytidectomy. Although many of these interventions have promising results, the current literature supports the senior author's (R.J.R.) experience that an evidence-based, multimodal approach is ideal to minimize the rates of hematoma after rhytidectomy.